Dietary strategies for preventing and managing obesity through evidence-based nutritional interventions - Stephen Olaide Aremu; Blessing Akute; Dorcas Oluwakemi Aremu; Caleb Zando; Esther Damilola Aremu; Omagu Julia Nwachukwu; Mary Omolola Omosebi; Victoria Oluwatosin Akute; Stephen Tokunbo Oluwole; Abdillahi Abdi Barkhadle; Matthew Olaleke Aremu (Discover Public Health)
Abstract Globesity, a term denoting the escalating global obesity epidemic, represents a significant public health crisis with severe health and economic ramifications. The prevalence of obesity has surged worldwide, transcending socioeconomic and geographic boundaries, and is a major contributor to non-communicable diseases such as type 2 diabetes, cardiovascular diseases, and certain cancers. This crisis is driven by multifaceted factors, including sedentary lifestyles, urbanization, dietary transitions, and behavioral influences. As obesity rates continue to rise, dietary interventions emerge as crucial and modifiable strategies for prevention and management. Unlike pharmacological and surgical treatments, dietary modifications offer sustainable and accessible solutions to address obesity at both individual and population levels. This comprehensive review examines various dietary approaches to mitigate the burden of globesity. The review synthesizes evidence from peer-reviewed literature, focusing on macronutrient-specific diets (e.g., low-carbohydrate, low-fat), holistic dietary patterns (e.g., Mediterranean diet, intermittent fasting), and behavioral modifications (e.g., mindful eating). A structured literature search was conducted using PubMed, Scopus, and Web of Science, incorporating relevant keywords and MeSH terms. Studies meeting predefined inclusion criteria were analyzed through thematic synthesis, integrating insights into the mechanisms of dietary interventions, such as their effects on energy balance, hormonal regulation, and gut microbiota. Findings indicate that whole-food, nutrient-dense diets, coupled with reduced consumption of ultra-processed foods, play a pivotal role in weight management and metabolic health. Additionally, culturally adaptable and sustainable dietary strategies enhance adherence and long-term effectiveness. The review underscores the importance of integrating dietary interventions with public health policies, community initiatives, and education to create supportive environments for healthy eating. Addressing knowledge gaps and tailoring dietary approaches to diverse populations remain essential for combating globesity. This review highlights the critical role of dietary strategies in curbing obesity and informing policy and clinical practice to foster healthier societies worldwide.